How to Penetrate the Wall of an Unintentionally Deployed Wallstent in the External Carotid Artery for Stenting of an Internal Carotid Artery Lesion - Hashemi, Arash; Serati, Alireza; Ahmadieh, Arsis; Khalilipur, Ehsan; Ghaffari, Lida; Movahed, Mohammad Reza (International Journal of Angiology, 2024)
Carotid artery stenting is increasingly performed among patients with proper indications for carotid artery revascularization. It has a low complication rate with a short recovery time. In this case, we report a new complication due to unintended stent deployment in the external carotid artery covering the ostium of the internal carotid artery requiring penetration and stenting of the deployed Wallstent wall to advance the second stent in the proper position in the internal carotid artery.
Keywords: complications; carotid intervention; stenting; carotid stenting; wall stent; unintended deployment; complication